Magnetic properties and magnetic mineralogy of selected young volcanics from diﬀerent places of the Earth globe - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2009)
The contemporary, historical and recent volcanic rocks were studied. An in- tention of the work was to identify a presence of the so-called low-temperature oxidized titano-maghemite (Ti-Mgh) phase (if any) in the young volcanic rocks. In the previous works it has been revealed that this phase is a source of the self-reversal remanent mag- netization (RM) in volcanic rocks (Orlický, 2006, 2009; Orlický and Funaki, 2008). The thermal demagnetization of the samples and inducing of partial thermoremanent magne- tization (PTRM) of the samples in the laboratory ﬁeld, the measurements of the change of magnetic susceptibility (κ) at selected temperature intervals of the compact samples and the measurements of the Curie temperatures and the study of behaviour of magnetic susceptibility (κ) of samples in the low and high temperature intervals were carried out. In the macroscopically evidenced oxidized basaltic scoria from the Tenerife volcano a small portion of the low-temperature oxidized Ti-Mgh phase was revealed. A small portion of the low-temperature oxidized phase was revealed also in the andesite from the Rainier volcano (20 000 years old). But a behaviour of magnetic susceptibility with temperature, characteristic for a presence of the low-temperature oxidized Ti-Mgh phase, was revealed in older basaltic scoria of the Death Valley (age either 700 000 years or more). All other 12 laboratory investigated volcanic rocks have not possessed the low-temperature oxidized Ti-Mgh phase.